A comparison of animal-related figures in milk and meat production and economic revenues from milk and animal sales of five dairy cattle breeds reared in Alps region. Issue 1 (14th December 2020) - Zanon, Thomas; König, Sven; Gauly, Matthias
Abstract: The objective of this study was to compare animal-related figures in milk and meat production and economic revenues from milk and animal sales over the last decade of the five most-common dairy cattle breeds in South Tyrol. Auction prices and milk performance control data were considered to calculate milk sales, animal sales and total revenue per cow of the respective breed between January 2009 and December 2019. Results highlight a stepwise substitution of Brown Swiss breed by Simmental breed over the last decade. This is probably related to the greater animal sales and greater total revenue per cow thanks to the dual-purpose characteristics in latter. No significant trend towards the breed Holstein-Friesian was observed although cows of this breed were shown to produce the highest milk yield (MY) per lactation and generated the highest total revenue per cow. Moreover, the local breeds Pinzgauer and Alpine Grey were able to compete in sense of importance as the number of cows remained mainly unaltered over the last decade. Thus, results indicate that although less productive, in sense of MY, local dual-purpose breeds seem to be of high interest for dairy farming systems in an alpine area as the decision for breeds is obviously not only driven by farm income. Highlights: Holstein-Friesian is the most productive cattle breed considering milk production per lactation Simmental breed has a similar milk yield as Brown Swiss breed but received higher auction prices for calves and cull cows than latter Pinzgauer and Alpine Grey cows can compete with other breeds thanks to their dual-purpose characteristics, adaptability to alpine farming systems and additional subsidies